Perceptions of childhood immunization in São Paulo: a quantitative-qualitative cross-sectional study - Costa, Lucas de Brito; França, Carolina Nunes; Nali, Luiz Henrique da Silva; Colombo-Souza, Patrícia; Novo, Neil Ferreira; Juliano, Yára (São Paulo Medical Journal, 2025)
BACKGROUND: Vaccination hesitation spans from historical diseases such as smallpox to the current challenges with the coronavirus disease (COVID-19). In Brazil, vaccination faces obstacles related to trust and convenience. Despite the National Immunization Program, fear of adverse effects as well as misinformation challenge confidence in vaccines, and anti-vaccine movements have gained momentum. OBJECTIVES: This study investigated childhood vaccine refusal, including COVID-19 vaccines, by comparing the reasons for and sociodemographic differences between vaccinated individuals and those who hesitated or refused immunization. DESIGN AND SETTING: A cross-sectional study was conducted in São Paulo, Brazil, using questionnaires administered during pediatric consultations between January and April 2023. METHODS: This study investigated vaccine hesitancy and the attitudes of parents and caregivers of children (0–12 years) towards vaccines. The questionnaire was administered during routine pediatric consultations at three different locations, each with 50 participants for a total of 150 participants, to avoid selection bias. RESULTS: Marked differences were evident among caregivers in terms of sex, race, income, education, and religion, which influenced their attitudes toward vaccination. There was an increase in the refusal of seasonal vaccinations and a significant distrust of the efficacy of the COVID-19 vaccine (52%), with concerns about its side effects. Although most patients did not stop vaccination, significant delays occurred, especially in the clinical setting (58%). CONCLUSIONS: This study emphasizes the importance of childhood health decisions, indicating the need to build trust in vaccines, tailor health policies, and investigate the causes of distrust to promote childhood immunizations.